Optimal clustering for delay minimization - Rajaraman, Rajmohan; Wong, D. F. (30th ACM/IEEE Design Automation Conference, 1993)
This paper addresses the problem of circuit clustering for delay minimization, subject to capacity constraints. We use the general delay model, for which only heuristic solutions were known. We present an optimal polynomial time algorithm for combinational circuits under this model. Our algorithm can be generalized to solve the problem under any monotone clustering constraint.